Imprezy biegowe na obszarach wiejskich w Polsce a poziom uczestnictwa Polaków w kulturze fizycznej = Running events in rural areas in Poland and the level of citizen participation in physical culture - Poczta, Joanna; Malchrowicz-Mośko, Ewa (Journal of Education, Health and Sport, 2016)
Poczta Joanna, Malchrowicz-Mośko Ewa. Imprezy biegowe na obszarach wiejskich w Polsce a poziom uczestnictwa Polaków w kulturze fizycznej = Running events in rural areas in Poland and the level of citizen participation in physical culture. Journal of Education, Health and Sport. 2016;6(12):488-503. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.208486 http://ojs.ukw.edu.pl/index.php/johs/article/view/4079 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.12.2016. Revised 12.12.2016. Accepted: 19.12.2016. Imprezy biegowe na obszarach wiejskich w Polsce a poziom uczestnictwa Polaków w kulturze fizycznej Running events in rural areas in Poland and the level of citizen participation in physical culture Joanna Poczta, Ewa Malchrowicz-Mośko Katedra Humanistycznych Podstaw Turystyki i Rekreacji Wydział Turystyki i Rekreacji Akademia Wychowania Fizycznego im. E. Piaseckiego w Poznaniu Dr Joanna Poczta Dr Ewa Malchrowicz-Mośko STRESZCZENIE Celem artykułu jest wykazanie potencjału obszarów wiejskich do aktywności sportowo-rekreacyjnej w Polsce. Zagospodarowanie tego potencjału może natomiast wypełnić niszę i mieć utylitarny wpływ na kształtowanie postaw wobec zdrowia i kultury fizycznej jej uczestników, a także mieszkańców obszarów recepcji turystycznej. W artykule wskazano, że polityka zdrowotna w coraz większym zakresie koncentruje się na promowaniu prozdrowotnego modelu zachowań, który wspiera osiąganie dobrego stanu zdrowia ogółu populacji oraz, że interwencje z zakresu promocji zdrowia poprzez aktywność fizyczną są coraz częściej ukierunkowywane na zmiany w stylu życia i dotyczą również czasu wolnego i turystyki, w ostatnim czasie coraz częściej także na obszarach wiejskich w kraju. Słowa kluczowe: wydarzenia sportowe, imprezy biegowe, turystyka sportowa, obszary wiejskie, promocja zdrowia, kultura fizyczna. ABSTRACT The aim of this article is to demonstrate the potential of rural areas for sports and recreation activities in Poland. Development of this potential may, however, fill a niche and have a utilitarian influence on attitudes towards health and physical culture of the participants, as well as residents of reception areas. The article indicated that health policy increasingly focused on promoting healthy behavior model, which supports the achievement of a good state of health of the general population and that interventions in health promotion through physical activity are increasingly being channeled to changes in lifestyle and also concern leisure and tourism, recently increasingly also in rural areas in the country. Key words: sporting events, running events, sports tourism, rural areas, health promotion, physical culture.